Cultural periodicals and structuring of the field : the case of Peuples noirs, peuples africains (1978-1991) - (:unkn) unknown (My University, 2019)
This work is within a double framework of research: on the one hand, the study of the role of the cultural periodicals in the total structuring of the literary fields at the time contemporary ; in addition, historical analysis of the typical case of the African literatures in France and their positioning for the period considered, starting from the assumption of the existence of the under-field sometimes called “the Africa-on-Seine” (Cazenave, 2003). The basic corpus is consisted the review Peuples noirs-peuples africains (1978-1991). At the same time political and literary, this periodical positions like the spokesperson of the African people. One will wonder about the capacity of this periodical to get a place in the French field and to change the rules them, starting from a dominated position and according to the procedures of already studied emergence or fan-in addition, generally for works or authors, but also for fields articulated within one (poly) - system. The analysis will consist in studying the review Peuples noirs-peuples africains. Initially, one will examine his collaborators, his networks of readers and his supports institutional. One will analyze, then, his contents and finally his leading policy. As far as possible, we will also try to exploit the archives available. As assumption, we will consider also a comparison, which will be more or less developed during our work, with the competitor periodicals of the time, such as Présence africaine.
Keywords: African Research